The impact of AI tools on software development practices and programmer productivity / Elly Johana Johan ... [et al.] - Johan, Elly Johana; Mohamed Yusoff, Syarifah Adilah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina (Unit Penerbitan JSKM, 2025)
The integration of Artificial Intelligence (AI) tools into software development has revolutionized traditional programming practices, significantly enhancing programmer productivity. This article explores the transformative impact of AI tools across various dimensions of software development, including code completion, bug detection and fixing, code refactoring, learning and adapting, automated testing, and natural language processing (NLP). AI-powered code completion tools like GitHub Copilot and PCR-Chain streamline coding by predicting and correcting code snippets, while bug detection systems like EBUG improve error resolution processes. Refactoring tools enhance software quality by automating repetitive tasks and providing optimization insights. AI's adaptive capabilities allow tools to learn user preferences, improving suggestion accuracy and usability. Additionally, automated testing frameworks leverage AI to optimize and expedite testing workflows, ensuring software reliability. The advancements in NLP have further enabled natural language-guided programming and documentation generation. Despite these advancements, challenges such as ethical concerns, reduced problem-solving skills, and usability issues persist, requiring balanced and responsible integration. Overall, AI programming assistants present immense potential to augment human capabilities and reshape the future of software development.